Faktor-Faktor yang Berhubungan dengan Kejadian Anemia pada Ibu Hamil - Neshy Sulung; Najmah Najmah; Rostika Flora; Nurlaili Nurlaili; Samwilson Slamet (Journal of Telenursing (JOTING), 2022)
This study aims to determine the factors associated with anemia in pregnant women. The method used in this study is a descriptive-analytic study with a cross-sectional design. The results showed that most of the respondents (50.5%) were highly educated; 75.2% work as housewives; 74.2% have good nutritional status; 78.9% were irregular in taking blood supplement tablets; 84.4% had anemia. The bivariate analysis results showed that education, nutritional status, occupation, and regularity obtained p-values of 0.12; 0.22; 0.03; and 0.008. In conclusion, there is a relationship between work and regular consumption of blood-added tablets with anemia in pregnant women. Keywords: Anemia, Factors, Pregnant Women